Port economies and maritime trade in the Roman Mediterranean: 166 BC to AD 300 - Rice, C (2012)
This thesis focuses on the economies of Roman ports and their role in the facilitation and organization of maritime trade, combining both terrestrial and maritime archaeological evidence as well as literary and epigraphic material. The first half of the thesis examines Mediterranean ports from a panoptic level in order to address questions of systems of trade, connectivity and economic development. In doing so, I focus on three particular areas of material culture: ceramics, shipwreck cargoes (typically composed of amphorae, metal ingots or stone) and epigraphy. The second half of the thesis focuses on two case studies, southern Turkey and southern France. For each region, I explore the economic factors which led to the development of each region and the ways in which ports enabled this development. I consider the impact of landscape, the usage of natural resources and the extent of production for both local consumption and export. Importantly, I examine the regional connections of the two regions and their interactions within the wider Mediterranean. I develop a model for the development of ports along each coastline and their degree of integration into the trading network of the Roman Mediterranean. Building on this, it becomes possible to assess the extent and scale of extra-regional interaction and market integration. From the evidence presented in this thesis, I argue that ports were at the core of the Roman market economy and that the development of a port network allowed for the integration and interdependence of Mediterranean markets. This allowed for regional economic growth through the specialization in the production of goods for which a region had a comparative advantage.